Fertility status of peat soils after 15, 20 and 25 years of oil palm (Elaeis Guineensis) plantation operation / Azhari Baharin - Baharin, Azhari (Faculty of Plantation and Agrotechnology, 2018)
The fertility status of peat soil changed after being planted with oil palm tree for several years. This study intends to compare the nutrient status of peat soils planted with oil palm tree after 15, 20 and 25 years of operation. In this study, soil samples of peat soils were collected at FELCRA Berhad Sungai Manila, Perak by using random sampling method. 30 samples were taken from different areas of 15 years, 20 years and 25 years planting oil palm tree and it’s were analyzed for their physical and chemical properties. The results showed that the colors between the three areas are similar which is very darks greyish brown (10YR 3/2). Soil bulk density is considered low (0.35 g/cm³) at area 15 years planting oil palm tree compared to others area. Area of 25 years is more acidic compared to other areas and it is have high of phosphorus content compared. Based on this study, it is suggested that management of plantation must considered all factors such as applying fertilizer to grow oil palm tree for proper management at peat lands.